Magnesium alloy composite coatings: In vitro study of cytotoxicity, adhesion, cellular structure and function - Natalya G. Plekhova; Polina A. Novikova; Ivan N. Chernenko; Aleksandra K. Stepanyugina; Olga V. Shevchenko; Valeria S. Marchenko; Andrey S. Gnedenkov; Sergey L. Sinebryukhov; Sergey V. Gnedenkov; Valentin B. Shumatov (Russian Open Medical Journal)
Background — Synthesis of novel grafts and biomaterial substitutes for bone reconstruction and study of their properties confirmed that the ideal material for this purpose has not yet been developed. Further efforts are needed to create contemporary biocompatible implants. It was shown that degradable biomaterials such as magnesium (Mg) alloys have potential clinical applications for bone reconstruction. However, poor resistance of Mg alloys to corrosion is a serious obstacle to their clinical use. This study aimed at investigating the biocompatibility and potential application of novel multifunctional self-healing coatings on Mg alloys to ensure stable performance of Mg implants in clinical settings. Methods — We studied a magnesium-based Mg MA8 alloy samples both with and without coatings containing hydroxyapatite, Ca10(PO4)6(OH)2. The latter were obtained by plasma electrolytic oxidation (PEO) and included cerium (Ce) and polycaprolactone (PCL). Toxicokinetic properties, cell adhesion, cytocompatibility and cellular enzyme activity were assessed after contact with the composite coating covering Mg. Results — The highest numbers of viable fibroblasts and tumor cells from the HeLa cell culture were observed after contact with Mg+PEO. Moderate cytotoxicity was found for the hydroxyapatite hybrid coating including cerium oxide (CeO2) and PCL. The variability of the parameters for these samples was similar to the variability of the parameters for intact cells and cells in contact with titanium, which showed minimal cytotoxic effects. Compared with copper, which had high cytotoxic activity, the values for the studied samples were significantly lower. After 30 minutes of exposure to Mg, a large number of agglomerates of rounded cells with numerous folded and filiform pseudopodia were observed. Cells on Mg+PEO surfaces were less aggregated and predominantly had fibrillar pseudopodia, also known as filopodia. Numerous rounded folds were observed on the surface of the Mg+PEO+CeO2+PCL hybrid coating, and cell groups were found in close contact resembling a syncytium. The number of stimulated cells on Mg+PEO decreased over time compared to the PEO-based hybrid coating on Mg with CeO2+PCL. Conclusion — The results of this study imply that the bioactive PEO composite coating with PCL and CeO2 modifies the Mg alloy surface by providing porosity that promotes strong cell attachment. These findings provide an alternative approach to develop multifunctional Mg-based implants and expand the biomedical applications of these materials. The data support the need for further investigation of the osteoinductive properties of coatings on biodegradable Mg implants.